Dampak Pembayaran Non Tunai Terhadap Percepatan Perputaran Uang Di Indonesia - Rahayu, Sri; Nugroho, Ris Yuwono Yudo (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2020)
Electronic Money Users and Card-Based Payment Instruments are rapidly increasing in the economy. Specifically, the study aims to determine the effect of the development of electronic money (e-money), and Card-Based Payment Instrument to accelerate the velocity of money in Indonesia. The analysis uses the Autoregressive Distributed Lag (ARDL) model to examine the existence of the short-term model, or if there is cointegration, then estimate the long-term relationship and the error correction model. The conclusion of the study that there is cointegration between the acceleration of the velocity of money, with electronic money and the Card-Based Payment Instrument (APMK) means that in the long run, electronic money and card-based payment instruments significantly influence the acceleration of the velocity of money. In the short term, the development of electronic money and card-based payment instruments significantly influences the acceleration of the velocity of money, with different direction coefficient patterns. This different direction happens because both of them are money substitutes held by the community. In the long run, the two variables significantly influence the acceleration of the velocity of money in different directions. APMK has a positive effect, while electronic money has a negative sign on the acceleration of the velocity of money. Suggestions include the need to increase the use of electronic-based payments more broadly, and further research using the development of currency and demand deposits, as well as national income.